Thermophysical Insights into the Anti-Inflammatory Potential of Magnetic Fields - Umberto Lucia; Giulia Grisolia; Antonio Ponzetto; Thomas S. Deisboeck (Biomedicines)
Background: Inflammation is caused by an excess of Sodium ions inside the cell. This generates a variation in the cell’s membrane electric potential, becoming a steady state from a thermodynamic viewpoint. Methods: This paper introduces a thermodynamic approach to inflammation based on the fundamental role of the electric potential of the cell membrane, introducing an analysis of the effect of heat transfer related to the inflammation condition. Results: The direct proportionality between the reduction in temperature and the increase of Na+ outflow may ameliorate the inflammation cascade. Conclusions: Based on these ion fluxes, we suggest the consideration of a ‘companion’ electromagnetic therapeutic wave concept in support of the present anti-inflammatory treatment.